ANALISIS KETIMPANGAN PENDAPATAN PERKAPITA DI KOTA PEKANBARU TAHUN 2013-2019 - Siti, Rahayu Asih; H.B, Isyandi; Wahyu, Hamidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study was to determine the inequality analysis of per capita income in Pekanbaru City in 2013-2019. The data used in this study are secondary time series data. The analytical method used is descriptive quantitative with williamson Index and multiple linear regression using SPSS. The analysis shows that the level of income inequality in Pekanbaru City is still high because it is above the williamson index limit value of 0.4. The economic growth variable has a negative and significant effect on income inequality while the investment variable has no effect on income inequality.Keywords: Income Inequality, Economic Growth and Investment